DiGeorge syndrome presenting with seizure in neonatal period: a case report - Begum, Noorjahan; Mohsin, Fauzia; Sufian, Abu; Islam, Nasreen; Nahar, Jebun; Mollah, Mohammad Abid Hossain (BIRDEM Medical Journal, 2021)
DiGeorge syndrome is caused by a micro-deletion of chromosome 22q11.2 that disrupts development of the third and fourth pharyngeal pouches during early embryogenesis. Other structures forming at the same period are also frequently affected. So, the phenotypic spectrum shows a wide variability. In this case report, we describe a 1-month and 24-day old male child who presented with history of recurrent afebrile seizure and noisy breathing since early neonatal period. He had history of repeated chest infections. On examination, patient had stridor, facial dysmorphism, pectus excavatum and clinical features of pneumonia. Investigations revealed hypocalcaemia, hypoparathyroidism, consolidation on X-ray chest and cellular immunodeficiency. Echocardiography findings were normal. Fluorescent in situ hybridization (FISH) was performed which confirmed the diagnosis 22q11.2 deletion. Birdem Med J 2021; 11(2): 128-132